Urdu ka guldasta (khususi isha$1 (Bat): gainda class 2s - Fozia, Ahsan Farooqui (Oxford University Press Karachi, 2022)
"Urdu ka Guldasata: Gainda Class 2" builds upon the foundation laid in the previous book, offering more advanced lessons in Urdu language arts. This textbook focuses on developing reading fluency, writing skills, and comprehension abilities in young learners. Through a variety of exercises and real-world examples, students are encouraged to apply their knowledge of Urdu grammar and vocabulary.